Reconciling Organic-Medical and Psychological Paradigms in the Study of Counselors’ Cognitive Flexibility: a Critical Literature Review - Cahya Irani, Luthfita; Hidayah, Nur; Ramli, M. (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
Cognitive flexibility of a counselor or therapist refers to their ability to adapt their cognitive approach to the unique needs and circumstances of their clients. This requires the ability to recognize and adapt to the unique cognitive processes and thought patterns of each individual. In the contextual development of cognitive flexibility in counselors, the organic-medical paradigm and the psychological paradigm have led to a revolution. The existence of these two paradigm perspectives necessitates a unique study that bridges the concept of understanding the two paradigms holistically in order to enhance the cognitive flexibility of the counselor. The purpose of this study is to investigate where the organic-medical paradigm and the psychological paradigm intersect when examining the cognitive flexibility of the counselor. The research design was quantitative and based on a critical literature review. The research focuses on three major components: (1) context issues regarding counselor cognitive flexibility from the perspective of the medical organic paradigm and psychological paradigm; (2) issues regarding the main implicit and boundary problems of counselor cognitive flexibility on professional work performance based on literature research data; and (3) the most promising questions for future research development. In this article, the research findings are discussed further.